دور العملة الاوربية الموحدة في إعادة صياغة النظام النقدي الدولي - د. فواز جارالله الدليمي; د. بشار احمد العراقي (PROSPECTIVE RESEARCHES, 2023)
Euro, the legitimate son of European Monetary System (EMS) has calledoff so many opportunities to deny the commencement of a new stage of the European and international economic relation. The ability of the European currency ingathering the capabilities of twelve countries in Europe led the changes in political and economic trends regionally and globally. Euro has caused the birth of a new international Monetary System (IMS). The study tries to bring about the role of Euro in this new (IMS) by clearing up the ability of this currency in breaking the ring of US dollar which binds the current (IMS) and how it has been transformed into a dual system whom is reformed, developed, and guided by both Euro and US dollar after the latter failure to improve those objectives.